Proteomics validate circulating GDF-15 as an independent biomarker for COVID-19 severity - Bu, Simeng; Royston, Léna; Mabanga, Tsoarello; Berini, Carolina A.; Tremblay, Cécile; Lebouché, Bertrand; Cox, Joseph; Costiniuk, Cecilia T.; Durand, Madeleine; Isnard, Stephane; Routy, Jean-Pierre (Frontiers in Immunology, 2024)
Growth differentiation factor 15 (GDF-15) was originally described as a stress-induced cytokine, and a biomarker of aging and cardiovascular diseases. We hypothesized that circulating GDF-15 would be associated with COVID-19 disease severity. Herein, we explored this hypothesis in a large cohort of COVID-19 patients.Blood samples were collected from 926 COVID-19 adult patients and from 285 hospitalized controls from the Biobanque Québécoise de la COVID-19 (BQC19). COVID-19 severity was graded according to the WHO criteria. SOMAscan proteomics assay was performed on 50µL of plasma. ELISA were performed on 46 selected participants with left-over plasma to validate differences in plasma GDF-15 levels. Statistical analyses were conducted using GraphPad Prism 9.0 and SPSS. P values < 0.01 were considered significant.Proteomics showed that plasma GDF-15 levels were higher in COVID-19 patients compared to hospitalized controls. GDF-15 levels increased with COVID-19 severity. COVID-19 patients presenting with comorbidities including diabetes, cancer, chronic obstructive pulmonary disease (COPD) and cardiovascular disease had higher GDF-15 levels. ELISA revealed significant elevation of GDF-15 until 30 days after hospitalization. Plasma GDF-15 elevation was correlated with older age. Moreover, GDF-15 levels correlated with pro-inflammatory cytokine interleukin-6 (IL-6) and inflammation marker C-reactive protein (CRP) as well as soluble levels of its putative receptor CD48. No association was established between anti-SARS-CoV-2 IgG levels and plasma GDF-15 levels.This study confirms GDF-15 as a biomarker for COVID-19 severity. Clinical evaluation of GDF-15 levels could assist identification of persons at high-risk of progressing to severe disease, thus improving patient care. GDF-15, COVID-19, SARS-CoV-2, proteomics, BQC19 Briefly, participants were recruited at the hospital and invited to participate between March 2020 and August 2021. Patients with SARS-CoV-2 diagnosis validated by RT-PCR or disease presentation were included. Medical history and clinical data were obtained from questionnaires and medical charts, and blood was collected at several timepoints.After selecting for data from adult participants, we considered samples, clinical and proteomics data from 926 adults diagnosed with COVID-19 and 285 hospitalized controls. COVID-19 was